Liver Injury Associated with Antituberculosis Medications - Mustika, Syifa; Susanti, Lia (Universitas Airlangga, 2025)
Tuberculosis remains a major global health concern, with a sharp increase in new cases in 2022, exceeding the prevalence before the coronavirus disease 2019 (COVID-19) pandemic. Conventional antituberculosis therapy, comprising a combination of first-line medications, is essential for controlling tuberculosis. However, more than 7% of patients undergoing treatment may develop drug-induced liver injury (DILI), mainly from isoniazid and rifampicin. This literature review aimed to evaluate DILI in tuberculosis, focusing on its causes, diagnosis, and management. Several factors, including age, sex, genetic predisposition, and pre-existing liver conditions, affect the occurrence of antituberculosis DILI. Advanced age and being female are significant risk factors for severe liver injury. Diagnosing DILI requires careful differentiation from other hepatic disorders, as its clinical presentation may include symptoms such as jaundice, abdominal pain, and elevated liver enzyme levels. Early detection relies heavily on liver function tests and clinical assessments. Managing DILI involves promptly discontinuing the offending drug, closely monitoring the patient, and gradually reintroducing medications, prioritizing less hepatotoxic options, such as rifampicin. Hepatoprotective agents and alternative drug regimens, particularly those excluding pyrazinamide, may be used to mitigate the risk of liver injury. The rise in tuberculosis cases in 2022 underscores the ongoing global burden of this disease and the critical need for effective treatment strategies. Tailored therapeutic approaches, comprehensive liver function monitoring, and early identification of DILI are vital for minimizing hepatotoxicity while ensuring successful tuberculosis management. Although hepatoprotective drugs and alternative regimens show promise, further research is necessary to optimize their application across diverse patient populations. Highlights: 1. This article presents a thorough evaluation of antituberculosis drug-induced liver injury, particularly concerning its causes, diagnosis, and management, highlighting the importance of a meticulous differentiation from other liver disorders through a comprehensive assessment of clinical indicators. 2. The literature review included studies utilizing advanced diagnostic tools for precise causality determination as well as innovative approaches, such as the selective omission of pyrazinamide or the integration of non-standard treatment protocols, which offer promising avenues to mitigate hepatotoxicity risk. 3. This literature review suggests that hepatoprotective agents, such as N-acetylcysteine, may have advantages due to their notable efficacy in preserving liver function, offering a proactive strategy for patient safety.